Agrobacterium-Mediated Transformation Of Wild ‘Senduduk’ (Melastoma Malabathricum) And Blue ‘Senduduk’ (Tibouchina Semidecandra) With Sense And Antisense Dihydroflavonol-4-Reductase Genes - Yong, Wilson Thau Lim (2007)

(untitled)
Flower industry has now emerged into a very profitable commercial enterprise. In Malaysia, Melastomataceae spp. is identified as a potentially important flowering ornamental and they are grown for commercialization purposes. However, only a few limited flower colours reduced their commercial value. In order to improve the qualities of plants as well as develop new varieties, genetic transformation was suggested. In this study, transformation of potentially flowering ornamental Melastoma malabathricum and Tibouchina semidecandra with sense and antisense dihydroflavonol-4-reductase (DFR) genes using Agrobacterium-mediated method was carried out. Minimal inhibitory concentrations of kanamycin on regeneration of M. malabathricum and T. semidecandra explants were obtained for the selection of putative transformants. Kanamycin concentrations at 500 and 400 mg/L were suggested to be used in the selection media for M. malabathricum shoot and node explants transformation, whereas 400 and 300 mg/L kanamycin were suggested to select for transformed shoots and nodes of T. semidecandra, respectively. Parameters such as bacterial strain, bacterial concentration, pre-culture period, co-cultivation period, immersion time, acetosyringone concentration and wounding type known to influence the transformation efficiency were assessed using green fluorescent protein (GFP) as marker. Results obtained were based on the percentage of GFP expression which was observed three days post-transformation. Agrobacterium tumefaciens strains LBA4404 and EHA105 at 1×107 cfu mL-1 (OD600nm 0.8) showed the highest infectivity on M. malabathricum and T. semidecandra, respectively. Four days of pre-culture and two days of co-cultivation were optimum for M. malabathricum transformation, while three days of pre-culture and co-cultivation were observed for T. semidecandra. Results also showed that 60 min of immersion with the addition of 200 μM acetosyringone gave the highest percentage of positive transformants for both M. malabathricum and T. semidecandra. Mild wounding of explants prior to transformation also significantly enhanced the transformation event but for M. malabathricum only. With the optimized transformation protocol established, plasmids pBETD10 and pBETD11, each harbouring DFR gene at different orientations (sense and antisense) and selectable marker nptII for kanamycin resistance, were used to transform M. malabathricum and T. semidecandra. The putative transformants were selected in the presence of kanamycin with their respective optimized concentration. Approximately 4.0% of shoots and 6.7% of nodes for M. malabathricum regenerated after transforming with pBETD10, whereas only 3.7% (shoots) and 5.3% (nodes) regenerated with pBETD11 transformation. For the selection of T. semidecandra, 5.3% of shoots and 9.3% of nodes regenerated with pBETD10 transformation, while only 4.7% (shoots) and 8.3% (nodes) regenerated after being transformed with pBETD11. Presence and integration of the sense and antisense DFR genes into the genome of M.malabathricum and T. semidecandra were confirmed by polymerase chain reaction (PCR), nucleotide sequence alignment and southern blot analysis. Regenerated putative transformants were acclimatized to glasshouse conditions. Approximately 31.0% pBETD10-transformed and 23.1% pBETD11-transformed M. malabathricum survived in the glasshouse, whereas 69.4% pBETD10-transformed and 57.4% pBETD11-transformed T. semidecandra survived. These putative regenerated transformants were subsequently grown on soil, awaiting flowering. In the present study’s time frame, both pBETD10- and pBETD11-transformed T. semidecandra had attained maturity and flowering stages. The colour changes caused by transformation were observed at the budding stage where greenish buds were produced by both T. semidecandra harbouring the sense and antisense DFR transgenes. Besides, production of four-petal flowers by putative T. semidecandra transformants also indicated the morphological difference from wild type plants.